2016
DOI: 10.1590/1518-8345.0860.2749
|View full text |Cite
|
Sign up to set email alerts
|

Taking a look to promoting health and complications' prevention: differences by context

Abstract: Objectives: to acknowledge and compare the health promotion and complications' prevention practices performed by nurses working in hospital and primary health care contexts. Methods: descriptive, exploratory and crosscutting study, performed with 474 nurses selected by convenience sampling. It was used a form that encompassed two categories of descriptive statements about quality in the professional exercise of nurses. This study had ethical committee approval. Results: the nurses' population was mainly women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
4
0
8
Order By: Relevance
“…Contrary to what was observed in the professional discourses, who understood that health promotion for adolescents occurs through preventive procedures (3) and healthy behavior orientation, without associating them with the socio-cultural context of the students and the development of criticality. But one of the components of the SHP has the purpose of promoting permanent education for the workers involved in the program (7) , thus bringing a possibility of improving training in a problematic and critical perspective.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Contrary to what was observed in the professional discourses, who understood that health promotion for adolescents occurs through preventive procedures (3) and healthy behavior orientation, without associating them with the socio-cultural context of the students and the development of criticality. But one of the components of the SHP has the purpose of promoting permanent education for the workers involved in the program (7) , thus bringing a possibility of improving training in a problematic and critical perspective.…”
Section: Discussionmentioning
confidence: 59%
“…A study performed in Portugal showed that the majority of nurses identify the health situations of the population and the resources of the patient, family and community, taking advantage of hospitalization to promote healthy lifestyles and to provide information generating cognitive learning and new abilities for this patient (3) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A promoção da saúde corresponde ao processo de capacitação de indivíduos e grupos para atuar na melhoria da sua qualidade de vida e saúde, incluindo uma participação maior no controle desse processo (15)(16) . A promoção da saúde não pode ser confundida com a prevenção de complicações decorrentes dos problemas potenciais e dos fatores de risco intrínsecos ou extrínsecos ao indivíduo (15)(16)(17)(18) .…”
Section: Discussionunclassified
“…Nesse contexto de possível confundimento, tem-se a reestruturação das práticas profissionais a Cienc Cuid Saude 2019 Out-Dez 18(4) e43864 partir da substituição da ênfase no paradigma biomédico pelo paradigma salutogênico visando a um cuidado coletivo, que considere as múltiplas e complexas relações e interações sociais. Esse processo requer adaptação individual e desenvolvimento de competências profissionais para promover nos sujeitos conhecimento, habilidades, atitudes e consciência necessários para um autocuidado eficiente (17)(18)(19) .…”
Section: Discussionunclassified